Constraints on the tectonic evolution of the southern central Asian orogenic belt from early Permian–middle Triassic granitoids from the central Dunhuang orogenic belt, NW China. (1st June 2020) - Feng, Lamei; Lin, Shoufa; Li, Longming; Davis, Donald W.; Song, Chuanzhong; Li, Jiahao; Ren, Shenglian; Han, Xu; Ge, Yanpeng; Lu, Kejia
Graphical abstract: Highlights: The central Dunhuang Orogenic belt (DOB) can be split into two contrasting terranes. The granitoid rocks were emplaced in two phases: ca. 284–275 Ma and ca. 255–238 Ma. The two phases of granitoids are arc-related and post-collisional rocks, respectively. Abstract: The Dunhuang orogenic belt (DOB), located in the southern Central Asian Orogenic Belt (CAOB), exposes Precambrian and Paleozoic intrusive-metamorphic rocks. To better understand its evolution, we carried out detailed petrological and geochronological investigations on the major lithologies of the central DOB. The central DOB can be divided into two terranes, the north and the south, with contrasting geological history. The north is characterized by Precambrian crystalline rocks (ca. 3.1–1.6 Ga) overprinted by Devonian tectono-thermal events. The Precambrian rocks show evidence for major juvenile crust growth with additions of older crustal materials at 2.7–2.5 Ga, a major crustal reworking event at 2.0–1.9 Ga, and juvenile additions with minor crustal reworking at 1.8–1.7 Ga. In contrast, the south is characterized by early Devonian (ca. 406 Ma) TTG-gneiss and amphibolite gneiss, and some Late Paleozoic–early Mesozoic granitoid rocks (ca. 284–238 Ma). The Late Paleozoic–early Mesozoic granitoid rocks from the south were emplaced in two phases: early Permian (ca. 284–275 Ma) and late Permian–middle Triassic (ca. 255–238 Ma). They belong to the high-K calc-alkaline I-type series which were generated from mixing juvenile materials with Mesoproterozoic continental crust. The early Permian and the late Permian–middle Triassic granitoid rocks are considered as arc/subduction-related and post-collisional rocks, respectively. These suggest that the final assembly of the DOB with the Beishan or final assembly within the DOB happened in the middle Permian (ca. 275–255 Ma). The DOB formed by accretion/collision of multiple terranes/microcontinents, similar to other areas in the CAOB.